Pengaruh Pemberian Air Rebusan Seledri Terhadap Kadar Asam Urat pada Lansia di Wilayah Puskesmas Menteng Kota Palangka Raya: The Effect of Giving Boiled Celery Water on Uric Acid Levels in the Elderly in the Menteng Community Health Center Area, Palangka Raya City - Syam’ani, Syam’ani; Susi, Susi; Ester, Ester (Jurnal Surya Medika (JSM), 2023)
Gout is a metabolic disease (metabolic syndrome) associated with high-purine diets and alcoholic beverages. This is because in the elderly there has been a decrease in the function of various organs of the body due to damage of cells due to the aging process. Celery which contains flavonoids, apigenin, apiin, alkaloids, tannins, and saponins has a significant effect on reducing uric acid levels in gout sufferers. This study aims to determine the effect of giving celery boiled water on reducing uric acid levels of the elderly in the Menteng Health Center, Palangka Raya City. This research method uses the Quantitative Quasi Experiment method with the design used is the One Group Pretest - Posttest Design without a control group but the first observation (pretest) has been carried out which allows researchers to examine the changes that occur after the Posttest experiment. The statistical test used the Wilcoxon test with a p value of 0.000 < 0.005. The results showed that there was an effect of giving celery boiled water on decreasing uric acid levels in the elderly in the Menteng Community Health Center, Palangka Raya City. Giving celery boiled water can be used to reduce uric acid levels in the elderly by giving 200 cc of celery boiled water regularly every morning and evening after meals.